Distribution, morphology and reproduction of the striped yellow-eared bat Vampyriscus nymphaea (Mammalia: Chiroptera) in Colombia - Rodríguez-Posada, Miguel E.; Ramírez-Chaves, Héctor E. (Instituto de Ecología, A.C., 2012)
We present information related on the distribution, morphology and reproductive biology of Vampyriscus nymphaea in Colombia, based in the analysis of voucher specimens housed in Colombia collections. The known distribution of V. nymphaea in Colombia previously restricted to the western lowlands of the Cordillera Occidental in the Pacific region is extended to the Caribbean region and to the north-eastern part of the Cordillera Occidental, lower Cauca River Basin of Colombia. Both external and the skull morphology of the species were homogeneous; the analysis of the secondary sexual dimorphism among specimens from the Pacific area do not show significant differences, although, the length of the tibia and the deep of the skull were proportionally larger in males, and the zygomatic width in females. Concerning to the reproductive biology, we suggest that the populations of V. nymphaea present a poliestric pattern along the year but without defined peaks.